2011
DOI: 10.1021/ja2032822
|View full text |Cite
|
Sign up to set email alerts
|

“Nanoscale Lattice Fence” in a Metal–Organic Framework: Interplay between Hinged Topology and Highly Anisotropic Thermal Response

Abstract: A thermoresponsive, 3D hinged metal-organic framework (HMOF-1) assembled from meso-tetra(4-pyridyl)porphine and CdI(2) exhibits a 3D "lattice fence" topology with extraordinary thermal expansion and shrinkage. A simple structural model is established to elucidate such a drastic thermal response. The hinged structure model presented here can also be applied to other "lattice fence" topologies with little or no modification, depending on the symmetry of the molecular building blocks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
98
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 141 publications
(102 citation statements)
references
References 26 publications
2
98
0
Order By: Relevance
“…Powder X-ray diffraction (PXRD) showed that 1 can retain framework integrity even after being heated at 673 K for 2 h (Supplementary Fig. S4), which is much higher than those for other organic and organic-inorganic hybrid solids showing large thermal expansion properties [4][5][6][7][8][9][10][11][12][13][14][15]21,22 . Gas sorption measurements showed that 1 cannot adsorb N 2 or O 2 at 77 K up to P/P 0 E1 but adsorb considerable CO 2 at 195 K, with an apparent Langmuir surface area of 188 m 2 g À 1 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Powder X-ray diffraction (PXRD) showed that 1 can retain framework integrity even after being heated at 673 K for 2 h (Supplementary Fig. S4), which is much higher than those for other organic and organic-inorganic hybrid solids showing large thermal expansion properties [4][5][6][7][8][9][10][11][12][13][14][15]21,22 . Gas sorption measurements showed that 1 cannot adsorb N 2 or O 2 at 77 K up to P/P 0 E1 but adsorb considerable CO 2 at 195 K, with an apparent Langmuir surface area of 188 m 2 g À 1 .…”
Section: Resultsmentioning
confidence: 99%
“…For example, a few flexible PCPs showed much larger thermal expansion than common solids because the open coordination frameworks are relatively flexible [4][5][6][7][8][9][10][11][12][13][14][15] . Whereas small positive thermal expansion (PTE, 0oao20 Â 10 À 6 K À 1 , a and b V for axial and volumetric thermal expansion coefficients, respectively) is an intrinsic property of common solids 16 , negative (NTE, ao0 K À 1 ) [17][18][19][20] , very large (|a|4100 Â 10 À 6 K À 1 ), tunable and other special thermal expansion behaviours are extremely rare and have received considerable theoretical and practical interest [21][22][23][24] , which may be rationally realized by PCPs.…”
mentioning
confidence: 99%
“…For a Electronic addresses: dearweili@gmail.com and shenke738@gmail.com b W. Li instance, some MOFs have been reported to exhibit negative linear compressibility (NLC) [42][43][44] and massive positive or negative thermal expansion (PTE and NTE). [45][46][47][48] Considering that MOF research is mainly dominated by synthetic chemists, a general introduction to the intrinsic links between chemistry and mechanics is of particular interest, as it will bridge the gap between chemistry and mechanical engineering. In this mini-review, we will discuss the mechanical properties of MOFs from the viewpoint of structure and chemical bonding by presenting a number of prototypical examples to demonstrate the strong connection between chemistry and mechanical behavior.…”
mentioning
confidence: 99%
“…Considering that this interaction is independent of the porphyrin unit, they believe this technique can be applied to various other porphyrin structures in order to construct MOFs with thermoresponsive behavior. 87 Demel et al created both a two-dimensional intercalated layer polymer and a MOF using tetra(4-sulfonatophenyl)porphyrin (TSPP) and a lanthanide-based octahedral oxometalate cluster (Fig. 34).…”
Section: Lee Et Al Produced a Mof By Mixing The Mn(iii) Derivative Omentioning
confidence: 99%
“…Proposed representation of lattice fence structure and expansion (right). 87 Liu et al used cucurbit [8]uril (CB8) and a tetranaphthylsubstituted porphyrin to create a self-assembled hyperbranched polymer. The structures were probed with 1 H NMR spectroscopy, electron paramagnetic resonance and isothermal titration calorimetry.…”
mentioning
confidence: 99%